Female gender images in adolescent magazine advertising - Napoli, Julie; Murgolo-Poore, Marie; Boudville, I. (ANZMAC, 2003)
Since the late 1960s, research into gender stereotypes in advertising has been prolific. The emergence of more magazines that target children and adolescents raises the question of whether the female images portrayed in these publications reinforce prevailing stereotypes of women and portray diversity in ethnicity. This study examines the female images shown by advertisers in the Australian editions of Barbie, Girlfriend and Dolly magazines. Findings indicate there is limited diversity in physical attributes as well as ethnicity of the models portrayed in these publications. Limitations are noted and future research issues are discussed.